Inter-local relations and trans-scaling through finance in Poland. Issue 2 (3rd April 2019) - Łukomska, Julita; Szmigiel-Rawska, Katarzyna
Abstract : Inter-local cooperation is difficult to measure. In Poland, however, the data-set concerning financial transfers between local government budgets (one of the most popular quantitative measures of cooperation) has never been described in scientific literature. This paper aims at contributing to fill this gap. On the basis of the budget expenditures of all Polish local governments, we applied two research methods: OLS regression and Heckman two-stage regression. The results show that the decision whether to get into cooperation, and the decision on the extent of involvement are driven by different factors.